Expression and Immunogenicity of M2e Peptide of Avian Influenza Virus H5N1 Fused to Ricin Toxin B Chain Produced in Duckweed Plants - Firsov, Aleksey; Tarasenko, Irina; Mitiouchkina, Tatiana; Shaloiko, Lyubov; Kozlov, Oleg; Vinokurov, Leonid; Rasskazova, Ekaterina; Murashev, Arkadii; Vainstein, Alexander; Dolgov, Sergey (Frontiers in Chemistry, 2018)
The amino acid sequence of the extracellular domain of the virus-encoded M2 matrix protein (peptide M2e) is conserved among all subtypes of influenza A strains, enabling the development of a broad-range vaccine against them. We expressed M2e from avian influenza virus A/chicken/Kurgan/5/2005 (H5N1) in nuclear-transformed duckweed plants for further development of an avian influenza vaccine. The 30-amino acid N-terminal fragment of M2, including M2e (denoted M130), was selected for expression. The M2e DNA sequence fused in-frame to the 3’ end of ricin toxin B chain (RTB) was cloned under control of the CaMV 35S promoter into pBI121. The resulting plasmid was used for duckweed transformation, and 23 independent transgenic duckweed lines were obtained. Asialofetuin-binding ELISA of protein samples from the transgenic plants using polyclonal anti-RTB antibodies confirmed the expression of the RTB–M130 fusion protein in 20 lines. Quantitative ELISA of crude protein extracts from these lines showed RTB–M130 accumulation ranging from 0.25–2.5 µg/g fresh weight (0.0006–0.01% of total soluble protein). Affinity chromatography with immobilized asialofetuin and western blot analysis of protein samples from the transgenic plants showed expression of fusion protein RTB–M130 in the dimeric form with a molecular mass of about 70 kDa. Mice were immunized orally with a preparation of total soluble protein from transgenic plants, receiving four doses of 7 μg duckweed-derived RTB–M130 each, with no additional adjuvant. Specific IgG against M2e was detected in immunized mice, and the endpoint titer of anti-M2e IgG was 1024. It was confirmed that oral immunization with RTB-M2e induces production of specific antibodies against peptide M2e, one of the most conserved antigens of the influenza virus. These results may provide further information for the development of a duckweed-based expression system to produce a broad-range edible vaccine against avian influenza.